Pumed Gainc y Mabinogi - Glyn, Peredur (Y Lolfa, 2022)
Forget everything about what you think is true. Rhiannon, Gwydion, Mathonwy - did you think that they are only myths? The 'Blue Book' has been rediscovered... strange creatures gather in the shadows... and forces beyond your understanding spread their claws to tear your reality to shreds. Intro – Rhagair – Y Llyfr Glas – Plant Llŷr – Yn y Croen Hwn – Y Llu – Yr Alaw – Arswyd y Maen – Y Gwyliwr ar y Tŵr – Rigantona – Datganiad am Farwolaeth y Parchedig Dafydd Isherwood – Cysgod y Grafanc – Lleu – Yr Arswyd yn y Darlun – 'Juvencus' – Tannau'r Delyn Ddu – Ar Allor Mathonwy – Drwy Waelod y Llyn Dienw – Nodiadau gan yr awdur: Arswyd Cosmig ac etifeddiaeth H.P. Lovecraft.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books